Budaya Organisasi, dan Kompensasi Terhadap Kepuasan Kerja Pegawai (Studi Kasus Divisi Mikro PT. Bank Mandiri Area Cikini Jakarta Pusat) - Lusiana, Lusiana; Indupurnahayu, Indupurnahayu; Amin, Akhmad Bakhtiar (Jurnal Manajemen, 2018)
This study aims to Analyzing the influence of the quality of human resources on job satisfaction of the employees of Area Micro Jakarta Cikini. Data collection techniques using questionnaires given to Cikini Area Micro Officers as many as 110 people. The hypothesis used is SEM (Structural Equation Modeling. Organizational culture relationship to job satisfaction in Micro Division of Bank Mandiri Area Cikini Central Jakarta of 0.757 with significance level 0,00 means that the influence of organizational culture variable on job satisfaction is very strong, the influence of quality of human resources to job satisfaction in Micro Division of Bank Mandiri Area Cikini Central Jakarta 0,877 with significance level 0,00, / influence of compensation to job satisfaction in Micro Division of Bank Mandiri Area Cikini Central Jakarta equal to 0,991 with significance level 0,00 mean that influence of variable of compensation to job satisfaction pertained strong strongly that job satisfaction will increase if compensation increases as well. Penelitian ini bertujuan menganalisa pengaruh pada tingkat kualitas sumberdaya manusia terhadap kepuasan kerja pegawai Mikro Area Jakarta Cikini. Tehnik Pengambilan data mengunakan kuesioner yang diberikan kepada Pegawai Mikro Area Cikini sebanyak 110 orang.hipotesa yang digunakan adalah SEM (Structural Equation Modelling.